Mobile Application for Mental Health (Afterglow) - Ishak, Farah Nuraqila; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2023)
Poor mental health has become a serious issue in many countries, Malaysia is also no exception especially among university students. Students with poor mental health may struggle to focus on their studies, particularly if they do not have a plan to deal with their condition. The purpose of this project is to develop a Mobile Application for Mental Health (Afterglow). The concept for this application formed through conversations regarding the stigma of mental health problems and access to counseling for students who may be afraid to seek help. Moreover, an iterative model was chosen to develop this application because it is easier to do testing and debugging. In addition, the iterative model is easily adaptable to meet the needs of the project. This application was developed in VS code using Dart programming language. Thus, the application developed is expected to help students control and manage emotions as well as increase their level of awareness of mental health issues in their daily lives.